Local eosinophils are associated with increased IgA subclass levels in the sinonasal mucosa of chronic rhinosinusitis with polyp patients - Hossein Aazami; Farhad Seif; Babak Ghalehbaghi; Pegah Babaheidarian; Alireza Mohebbi; Aslan Ahmadi; Majid Khoshmirsafa; Sahand Ghalehbaghi; Babak Behnam; Kobra Zinat Entezami; Zahra Madjd; Reza Falak (Allergy, Asthma & Clinical Immunology, 2020)
Abstract Background Chronic rhinosinusitis (CRS) describes an inflammatory condition affecting the sinonasal mucosa. As the immune system players such as immunoglobulins play prominent roles in the development of CRS, we aimed to investigate the expression of IgA subclasses and factors involved in IgA class switching in the sinonasal mucosa of CRS patients. Methods Specimens were collected from the sinonasal mucosa of the healthy controls and CRS patients. Histological assessments were performed by H&E and immunohistochemistry. Real-time PCR and ELISA methods were applied to measure gene expression and protein levels extracted from tissue samples, respectively. Results We observed that total IgA and subclass-positive cells were higher in the patient groups than controls. There was a significant correlation between the number of eosinophils and total IgA and subclasses-positive cells (Pv < 0.0001). The expression of CXCL13, BAFF, AID, and germline transcripts were increased in CRSwNP patients. In contrast to IgA2 levels, IgA1 levels were significantly increased in the sinonasal tissue of CRSwNP patients (Pv < 0.01). TGF-β was significantly elevated in the sinonasal tissue of patients with CRSsNP. Conclusions Increased protein levels of IgA subclasses and related antibody-producing cells were associated with elevated eosinophils in CRSwNP patients which may result in eosinophil pathological functions. Several therapeutic approaches might be developed to modulate the IgA production to ameliorate the inflammatory mechanisms in CRSwNP patients.